2018
DOI: 10.15326/jcopdf.5.2.2017.0159
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Dental Health Correlate with Daily Respiratory Symptoms in COPD

Abstract: Background: Poor dental health occurs in patients with chronic obstructive pulmonary disease (COPD); some evidence suggests that it may correlate with lower forced expiratory volume in 1 second (FEV1) and 6-minute walk distance, and an increased rate of exacerbations. However, there is no data that examines how dental health may impact the daily respiratory symptoms that COPD patients experience. We prospectively studied indices of dental health and hygiene in patients with COPD and determined their impact on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…A meta-analysis of 14 observational studies by Zeng et al showed an association between periodontitis and COPD diagnosis with a pooled OR of 2.09 (95% CI: 1.48–2.91) 10. Published studies also show that COPD patients have fewer remaining teeth compared with healthy controls 2528. However, few studies have evaluated the relationship between COPD exacerbation rates with periodontitis and dentition status 1114…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 14 observational studies by Zeng et al showed an association between periodontitis and COPD diagnosis with a pooled OR of 2.09 (95% CI: 1.48–2.91) 10. Published studies also show that COPD patients have fewer remaining teeth compared with healthy controls 2528. However, few studies have evaluated the relationship between COPD exacerbation rates with periodontitis and dentition status 1114…”
Section: Discussionmentioning
confidence: 99%
“…COPD patients have few remaining teeth, more dental plaque, and worse oral health-related quality of life. 64,65 Additionally, COPD patients do not brush their teeth, use dental floss, or visit the dentist as frequently as those without COPD. 64,66 Whether these correlations, which are likely multifactorial, play a causative role in COPD pathogenesis is unknown.…”
Section: Oral Health and Pulmonary Diseasementioning
confidence: 99%
“…While a variety of healthcare professionals (respiratory therapists, family physicians, nurses, pulmonary technicians, etc.) are involved in caring for patients with COPD, dental providers are often overlooked 5 . Despite this gap in practise, the relationship between oral health and COPD has been explored in scientific, clinical, and educational domains, pointing to a vital need for integrating dental care into COPD treatment 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the microbiome in both the lung and oral cavity is similar and connected through a bi-directional relationship 5,6 ; a pathogen exchange between the lung and oral cavities occurs through saliva aspiration and hematogenous spread 6 . Infected teeth or gums act as a reservoir for anaerobic bacteria that provoke respiratory symptoms like wheezing, and the same bacteria can also be isolated in infected lungs 5,6 . The most common dental condition associated with COPD is periodontitis: a chronic inflammatory disease of the periodontal tissue, or gums, caused by bacterial infection [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation